2021
DOI: 10.3390/buildings11040173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Density Loss in Anobiid Infested Pine Using X-ray Micro-Computed Tomography

Abstract: The present study aims at evaluating the impact of anobiid damage on pine timber elements. Anobiid attack produces a diffuse damage of the elements with a set of tunnels in random directions and sizes, thus confusing quantification. Therefore, a method was developed based on X-ray micro-computed tomography (μ-XCT) to obtain, for naturally infested timber samples, an empirical correlation between lost material percentage (consumed by beetles) and timber apparent density (original, before degradation—OTD and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[107] Data acquisition is a timeconsuming and complicated task, which contributes to increasing the scan time, reconstruction time, and data size (highresolution images). [105] The XCT method is superior to the XRR method because it reveals specific and subtle details. [108] The XCT machine is a fixed, heavy, and expensive instrumentation that emits high-level radiation and requires high-technical expertise.…”
Section: X-ray Computed Tomographymentioning
confidence: 99%
See 2 more Smart Citations
“…[107] Data acquisition is a timeconsuming and complicated task, which contributes to increasing the scan time, reconstruction time, and data size (highresolution images). [105] The XCT method is superior to the XRR method because it reveals specific and subtle details. [108] The XCT machine is a fixed, heavy, and expensive instrumentation that emits high-level radiation and requires high-technical expertise.…”
Section: X-ray Computed Tomographymentioning
confidence: 99%
“…The relative attenuation of X‐rays is dependent on the thickness, density, and chemical composition of the material [104] . The two‐dimensional images (projections) can be visualized as cross‐sectional slices in three planes (axial, coronal, and sagittal), [105] which describe the cumulative attenuation of the X‐ray beam through the object [106] . A computed‐reconstruction algorithm is applied to create a stack of the slices, producing a three‐dimensional image (tomogram) and mapping the spatial distribution of the internal structures of the objects [107] .…”
Section: X‐ray Techniques For Materials Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The scan data can be further processed to object volume, cross-sectional area, density, and porosity (Brock et al 2022). µ-CT has been used to study potential termite activities in wooden art frames and wood-boring beetles in maritime pine boards (Arbat et al 2021;Parracha et al 2021). The studies showed µ-CT's capabilities as a non-invasive method of identifying damage and providing a timeframe for planned maintenance of items (França et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diffuse attack of this insect makes the assessment of damage intensity more difficult [2]. In fact, despite being the most recurrent, this evaluation method presents too many uncertainties, since the number of internal galleries drilled by the insects is greater than the surface exit holes, which can lead to an underestimation of the level of degradation [3,4]. Regarding the reduction of the mechanical capacity caused by the anobiid infestation, in general, it is considered in the structural verification of old structural elements either by the reduction of the cross-section of the element (considering that the degraded zone does not present any strength) or assuming reduced mechanical properties for that element [5,6].…”
Section: Introduction 456mentioning
confidence: 99%